(untitled) (Revista Electrónica REDINE, 2021)
This analysis responds to a process of scientific and technical construction of a project framed in the education in values, which starting from a concrete reality, proposes a particular way of approaching this context, moving further away from the traditional research items and entering a more contiguous vision, starting from the potspositivist paradigm, phenomenological methodology, combining visions from ethnography, hermeneutics and grounded theory; that will allow in the end to propose a theory that promotes specific intervention programs for education in values ​​in Education. The purpose of this is to offer the university community a research route, not to follow as a rule, but to guide future social research, based on authors such as Martinez 2004, Garcia and Mínguez (2011), Glaser and Strauss (1967).